Positive Periodic Solutions for Neutral Delay Ratio-Dependent Predator-Prey Model with Holling-Tanner Functional Response - Guirong Liu; Sanhu Wang; Jurang Yan (International Journal of Mathematics and Mathematical Sciences)
By using a continuation theorem based on coincidence degree theory, we establish some easily verifiable criteria for the existence of positive periodic solutions for neutral delay ratio-dependent predator-prey model with Holling-Tanner functional response x'(t)=x(t)[r(t)-a(t)x(t-σ(t))-b(t)x'(t-σ(t))]-c(t)x(t)y(t)/h(t)y(t)+x(t), y'(t)=y(t)d(t)-f(t)y(t-τ(t))/x(t-τ(t)).